Preliminary Validation of the Hypertension Self‐Care Activity Level Effects (H‐SCALE) and Clinical Blood Pressure Among Patients With Hypertension. Issue 9 (25th June 2013) - Warren‐Findlow, Jan; Basalik, Debra W.; Dulin, Michael; Tapp, Hazel; Kuhn, Lindsay
Abstract : This study establishes preliminary validation of a measure that assesses hypertension self‐care activities with clinical blood pressure (BP). The Hypertension Self‐Care Activity Level Effects (H‐SCALE) was administered to patients with hypertension to assess levels of self‐care. Patients (n=154) were predominantly female (68.6%) and black (79.2%). Greater adherence to self‐care was associated with lower systolic and diastolic BP for 5 of the 6 self‐care behaviors. Medication adherence was correlated with systolic BP ( r =−0.19, P <.05) and weight management adherence was correlated with diastolic BP ( r =−0.22, P <.05) after controlling for other covariates. Increased adherence to recommended dietary practices was strongly correlated with higher systolic ( r =0.29, P <.05) and diastolic BP ( r =0.32, P <.05). The H‐SCALE was acceptable for use in clinical settings, and adherence to self‐care was generally aligned with lower BP. Assessment of hypertension self‐care is important when working with individuals to control their BP.